FISCAL EQUALIZATION WITHOUT CONVERGENCE: DYNAMIC PANEL AND DID EVIDENCE ON AN EAST–WEST CORE–PERIPHERY DIVIDE - Ahmad, Ahmad; Armawaddin, Muhamad; Mustam, Mustam (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2026)
A central puzzle in fiscal federalism is why large intergovernmental transfers and public investment can coexist with persistent spatial inequality. This study tests whether fiscal policy has differential effects on provincial inequality across Indonesia’s east–west core–periphery divide. We compile a balanced province–year panel of 33 provinces over 2010–2024 (N = 495) from official fiscal and socioeconomic statistics and apply two complementary strategies: (i) dynamic System GMM with region–fiscal interaction terms to address inequality persistence and potential endogeneity of fiscal variables, and (ii) a difference-in-differences design treating the post-2015 fiscal expansion as a quasi-experiment. Descriptive comparisons show statistically significant east–west disparities in inequality, poverty, GRDP, and human development. In dynamic models, inequality is highly persistent (preferred ρ = 0.8456), while capital expenditure, fiscal transfers, and their interaction terms with the Eastern indicator are statistically insignificant across five GMM specifications. Difference-in-differences estimates likewise show no differential post-2015 inequality reduction in Eastern provinces (λ ≈ −0.005; p ≈ 0.51–0.55). The novelty is a joint, region-heterogeneity test under dynamic identification combined with a policy-timing validation. The results imply that measurable fiscal equalization may depend on implementation capacity, spending composition, and longer adjustment horizons than annual provincial aggregates can capture.